Manajemen Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru di SD N 1 Mendak: Perencanaan dan Pengorganisasian sebagai Kunci Keberhasilan - Fadhilah Cahyaningrum; Sri Marmoah (Didaktika Dwija Indria, 2025)
This study aims to analyze the planning and organizing of the principal's leadership management in improving teacher performance at SD N 1 Mendak. The research method used is a descriptive qualitative approach with data collection techniques through interviews, observations, and document studies. The results showed that the principal has conducted leadership management planning by preparing a clear vision, mission, and goals. In addition, principals assign tasks and responsibilities according to teachers' competencies, as well as inform training and provide facilities for teachers to improve their pedagogical competence and professionalism. However, there are still obstacles in the uneven distribution of training and the lack of systematic monitoring and evaluation. Therefore, more effective strategies are needed to ensure equitable training opportunities for all teachers. The conclusion of this study emphasizes the importance of systematic and sustainable planning and organization of principals' leadership to improve teachers' performance in schools.